Karakteristik Rasm Dan Sumber Penafsiran Al-Qur’an
The use of the digital Qur'an is growing rapidly in the midst of society. The emergence of the digital Qur'an makes it easier for people to access the Qur'an by simply opening it from their mobile phone. This requires attention from academics, especially in the fields of the Qur'an and interpretation. In Indonesia, there are already agreed standard manuscripts, namely mus